Hubungan Explosive Power Otot Tungkai dengan Akurasi Smash pada Tim Bolavoli Putra Pendidikan Olahraga FKIP Universitas Riau - Andriansyah Andriansyah (Indra institute Research & Publication, 2021)
The form of this research is correlational research with the population of the Men's Volleyball Team for Sports Education FKIP Riau University. The sampling method in this study is a total sampling technique. Because the population is less or less than 100 people, the sample is taken from the total population. The instrument in this study was a test for measuring leg muscle explosive power with a vertical jump test using the MD jump tool and a smash accuracy test with a smash accuracy target test. Then the data was processed statistically, before the data was processed, a normality test was carried out using the Liliefors test at a significant level of 0.05. The hypothesis proposed is that there is a relationship between explosive power of leg muscles and smash accuracy in the Men's Volleyball Team for Sport Education FKIP Riau University. Based on the results of the research conducted, it can be concluded that the explosive power of the leg muscles has a significant relationship with smash accuracy, where from the normality test the data obtained are Lcount(x) 0.1000 while Lcount(y) 0.2061 and Ltable 0.220, so Lcount >The result is that Ho is rejected and Ha is accepted. From the results of the calculation of the product moment correlation between leg muscle power and Smash accuracy, it is obtained rcount 0.81 and rtable 0.532 as a result Ho is rejected and Ha is accepted, the contribution of the X variable to the Y variable is categorized as High. (4.9874 > 1.753) thus Ho is rejected and Ha is accepted. The explosive power element of the leg muscles explains the variability of r2 x 100% = 66% of the smash accuracy in volleyball and the rest is explained by other variables.